Data-Driven Approaches in Islamic Quality Management and Education Technology for Advancing Sustainable Development Goals - Elihami, Elihami; Masuwd, Mowafg Abrahem; Sheerly, Sheerly; Ismail, Ismail; Sitonda, Syawal; Sudirman, M. Yunus (FKIP Universitas Lampung, 2024)
Data-Driven Approaches in Islamic Quality Management and Education Technology for Advancing Sustainable Development Goals. Objective: This study investigates how Artificial Intelligence (AI) and data-driven approaches can transform quality management systems in Islamic education to advance the Sustainable Development Goals (SDGs). It explores AI's potential to enhance educational quality, accessibility, and administrative efficiency while addressing unique challenges and ethical considerations within the Islamic educational landscape. Method: A mixed-methods approach was employed, integrating literature reviews, case studies, and expert consultations. Quantitative analyses of student performance data were combined with qualitative insights from stakeholders in Islamic education to provide a comprehensive perspective on AI's impact on institutional quality management and educational technology applications.Findings: AI demonstrates considerable promise in enhancing Islamic educational institutions by enabling personalized learning, improving resource accessibility, and optimizing management practices. Its flexibility in accommodating diverse learning preferences and its capacity to engage students highlight its potential for supporting varied educational needs. However, challenges such as ensuring content reliability, mitigating algorithmic biases, and addressing ethical implications aligned with Islamic principles must be addressed for successful implementation.Conclusion: Data-driven and AI-enabled quality management strategies offer significant opportunities for Islamic education to meet SDG targets. Effective integration, however, requires alignment with Islamic ethical standards and dedicated oversight to balance technological innovation with foundational Islamic values. This study provides valuable insights for educators, policymakers, and developers aiming to responsibly leverage AI in advancing Islamic education toward sustainable and inclusive development. Keywords: islamic education technology, artificial intelligence (AI) in education, Quality management systems, sustainable development goals (SDGs) DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024109